2022
DOI: 10.3390/su14031901
|View full text |Cite
|
Sign up to set email alerts
|

Valuating Natural Resources and Ecosystem Services: Systematic Review of Methods in Use

Abstract: The relevance of an ecosystem approach, which involves addressing ecosystems as an object of research, economically evaluating ecosystem services, and including the existing variety of evaluation methods and their classifications for the estimation of nature’s value, was the focus of this study. So, the aim of the current research is to develop an evaluation theory by refining approaches and methods for the economic evaluation of natural resources and ecosystem services. The research object was the evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Following identification and prioritization of the ecosystem services at each site, we proceeded on to valuation based on the market price, avoided cost, and value transfer methods [47]. International experience in the economic valuation of natural resources and ecosystem services revealed that these methods are usually used when there is limited information access [48]. The first approach employs prevailing prices for goods and services traded in domestic markets [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following identification and prioritization of the ecosystem services at each site, we proceeded on to valuation based on the market price, avoided cost, and value transfer methods [47]. International experience in the economic valuation of natural resources and ecosystem services revealed that these methods are usually used when there is limited information access [48]. The first approach employs prevailing prices for goods and services traded in domestic markets [49].…”
Section: Discussionmentioning
confidence: 99%
“…In general, for the economic valuation of the prioritized ecosystem services in each region, we followed these steps (Figure 2): (i) identification of the main characteristics of the economic activity related to the ES under analysis (population, suppliers, and participants in the value chain); (ii) identification of the threats to the ES from sociocultural, institutional, and environmental perspectives; (iii) selection of an estimation strategy based on the threat(s) identified (in step (ii)) and information limitations; (iv) firstly, using the valuation approaches (price market based, avoided costs, and values transfer), calculation of the ES value based on two scenarios: one in which the local government does not pursue any conservation actions (status quo situation), and another in which the local government does take conservation actions (optimized situation) that Following identification and prioritization of the ecosystem services at each site, we proceeded on to valuation based on the market price, avoided cost, and value transfer methods [47]. International experience in the economic valuation of natural resources and ecosystem services revealed that these methods are usually used when there is limited information access [48]. The first approach employs prevailing prices for goods and services traded in domestic markets [49].…”
Section: Discussionmentioning
confidence: 99%
“…The hedonic price method estimates the economic value of pure public ecological products (e.g., environmental quality) based on individuals' willingness to pay for them. Additionally, scholars have extensively employed non-traditional valuation methods such as the factor income method, shadow pricing method, and market price method [37][38][39][40]. The factor income method is employed to estimate the future expected economic value of quasi-public ecological products or operational ecological products (such as land, water, wood, etc.)…”
Section: Eco-product Value Accounting and Value Realization 41 Eco-pr...mentioning
confidence: 99%
“…The development of the ES field of study is generalised from the studies by Daily (1997) and Costanza et al (1997). Initiatives such as the Millennium Ecosystem Assessment (MEA) Project (2005) and The Economics of Ecosystems and Biodiversity (TEEB) (Kumar, 2010) are milestones that have converted the concept of ES into a political instrument in order to achieve the sustainable use of natural resources (Macaskill & Lloyd-Smith, 2022;Ignatyeva et al, 2022). Thus, the valuation of ecosystem services aims to provide stakeholders with knowledge useful for policy design, strategy definition and ecosystem management by identifying services as well as their flow and relative importance to society (Mirici, 2022).…”
Section: Introductionmentioning
confidence: 99%